Effect of roughage to concentrate ratio of sweet sorghum (Sorghum biclor L. Moench) bagasse-based complete diet on nutrient utilization and microbial N supply in lambs - Kumari, N.N.; Reddy, Y.R.; Blümmel, Michael; Nagalakshmi, D.; Sudhakar, K.; Reddy, V.R.; Monika, T.; Pavani, M.; Reddy, M.S.; Reddy, B.V.S.; Reddy, C.R. (Springer, 2012)
An experiment was conducted to study the effect of roughage to the concentrate ratio of complete diets containing sweet sorghum bagasse (SSB), an agro-industrial by product, as sole roughage source on nutrient utilization in ram lambs. Twenty-four Nellore × Deccani cross ram lambs aged about 3 months (average body wt. 10.62±0.03 kg) were randomly allotted into four groups fed with CR-I (60R:40C), CR-II (50R:50C), CR-III (40R:60C), and CRIV (30R:70C) complete diets. The roughage to concentrate ratio did not affect the dry matter intake (in grams/day or grams/kilogram weight0.75). The crude protein (P<0.01) and ether extract (P<0.05) digestibility of ration CR-IV was higher than CR-I and CR-II rations, whereas, the digestibility of nitrogen-free extract and fiber fractions was similar among all the rations. Experimental diets were different (P<0.01) in digestible crude protein (DCP) content, in which the CR-I ration contained lower DCP value whereas CR-IV ration contained higher DCP value. The total digestible nutrients (TDN) and metabolizable energy (ME) values were comparable among all the experimental rations. The daily DCP intake (in grams/day) was lower (P<0.05) in lambs fed with CR-I ration compared to CR-III and CR-IV rations and it was comparable with CR-II ration. The TDN intake (in grams/day), digestible energy, and ME intakes (in megajoules/day) were similar among the lambs fed experimental rations with different SSB to concentrate ratios. The average daily DCP intake of lambs fed with CR-II, CR-III, and CR-IV rations met the requirements whereas, the daily TDN and ME intake was met by all the lambs. The lambs on all the diets were in positive nitrogen retention. The nitrogen balance expressed as grams/day was higher (P<0.05) in lambs fed with CR-III and CR-IV ration than those fed with CR-I ration. The daily calcium and phosphorus intake and balance were comparable on all the experimental rations. The total purine derivatives (in millimoles/day) were higher (P<0.05) in CR-III than CR-I and comparable with CR-II and CR-IV diets. The higher (P<0.01) microbial N supply (in grams/day) was observed in CR-III ration compared to other three rations and the efficiency of microbial synthesis was comparable among all the rations. It is concluded that sweet sorghum bagasse can be included in the complete rations at maximum level of 50 % as roughage source for rearing of ram lambs.